1909
DOI: 10.1007/bf01841955
|View full text |Cite
|
Sign up to set email alerts
|

Über die Bedeutung der Gewebe als Chlordepots

Abstract: Uber die Bedeutung der Gewebe als Chlordepots. u Valdemar Wahlgren -~ aus Upsala. ~) tIerausgegeben yon R. Magnus in Utrecht. 7*

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1926
1926
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(18 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…Over 100 years ago, Wahlgren and Padtberg noted that following increased dietary salt intervention the skin can serve as a salt depository [1, 2]. Approximately 40 years ago, Ivanova et al reported that huge amounts of Na + can be stored in the skin and linked to an enhanced sulfation of glycosaminoglycans in rats, which might serve as a negative charge capacitor for Na + [44].…”
Section: Local Salt Storage In the Skin Of Mice And Menmentioning
confidence: 99%
See 1 more Smart Citation
“…Over 100 years ago, Wahlgren and Padtberg noted that following increased dietary salt intervention the skin can serve as a salt depository [1, 2]. Approximately 40 years ago, Ivanova et al reported that huge amounts of Na + can be stored in the skin and linked to an enhanced sulfation of glycosaminoglycans in rats, which might serve as a negative charge capacitor for Na + [44].…”
Section: Local Salt Storage In the Skin Of Mice And Menmentioning
confidence: 99%
“…Traditionally, local salt storage in tissues was not considered to occur; consequently, studying local salt composition and its effect on tissues other than the kidney has been largely disregarded, although evidence to that effect already existed in 1909 [1, 2]. The generally accepted exception to this rule is of course the kidney, where large differences in electrolyte concentration are present and also required for the production of concentrated urine.…”
Section: Introductionmentioning
confidence: 99%
“…Na MR studies (12,13), (ii) a volume RF coil configuration at 7.0 T using a birdcage RF coil (C), and the proposed two-element transceiver RF coil array (D). The imaging protocol was adjusted (A-D): to achieve an in-plane spatial resolution of (3.0 x 3.0) mm 3 reported for state-of-the-art 23 Na MR studies (12,13) and (E): to facilitate an in-plane spatial resolution of (1.0 x 1.0) mm 3 while keeping the total scan time constant. SNR was determined for a region of interest placed in the phantom (marked in red) containing 25mM NaCl to resemble skin.…”
Section: Figurementioning
confidence: 99%
“…A reduced salt intake has been moved to be the primary adjustable behavior-related variable that should be adapted by every society worldwide (2). Over 100 years ago, Wahlgren found that the skin is a major storage depot for NaCl (3). This information was subsequently largely forgotten as clinical research focused on Na + regulation with regards to extracellular fluid volume in terms of a two-compartment model ultimately determined by renal function (4).…”
Section: Introductionmentioning
confidence: 99%
“…Large amounts of Na + are stored in the skin. Skin Na + storage can be induced experimentally by dietary salt (Ivanova et al, 1978; Padtberg, 1909; Titze et al, 2004; Wahlgren, 1909). Recent advances in magnetic resonance imaging allow for non-invasive quantification of Na + storage in the skin in humans and revealed that cutaneous Na + stores increase with age (Linz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%